Молитва Ахурамазде на древнеиранском языке среди арамейских надписей из Аребсуна - Боголюбов, M. H.
Bogoljubov, M. N.; An Old Iranian Prayer to Ahuramazda in Aramaic Characters. On the Undeciphered Inscription from Cappadocia; engl. Résumé S. 347.